The Analysis Study of Comparative Effectiveness of Different Therapies for Hyperthyroidism: A Comprehensive Systematic Review - Luthfiyya Syafiqa Tahany; Sinarty Hartanto (International Medical Journal Corp. Ltd, 2025)
Background: Hyperthyroidism is a condition characterized by excessive thyroid hormone production, which can lead to serious health complications if not properly managed. Available treatments—antithyroid drugs, radioactive iodine therapy, and thyroidectomy—vary in efficacy, safety, and appropriateness depending on individual patient factors. This review aims to systematically assess and compare these therapies to guide evidence-based clinical decision-making. Methods: This review followed PRISMA 2020 requirements and included only peer-reviewed, full-text English papers from 2015 to 2025. Editorials and review papers lacking DOIs were eliminated to ensure source dependability and citation tracking. To find articles that fit the review's study topic, PubMed, ScienceDirect, and SAGE Publications were extensively searched. Result: The initial database search identified more than 2,000 potentially relevant studies. Eight studies met the predefined inclusion criteria and were selected for detailed analysis through a structured three-phase screening and selection process. The studies underwent thorough evaluation for methodological quality and relevance, guaranteeing that the final synthesis relied on strong and high-quality evidence. The findings offer essential insights into the strengths and limitations of the comparative effectiveness of various therapies for hyperthyroidism. Conclusion: The effectiveness of hyperthyroidism treatments depends on individual patient factors, clinical conditions, and treatment goals. Antithyroid drugs are suitable for initial therapy, while radioactive iodine and surgery provide more definitive outcomes, each with distinct risks and benefits. This review highlights the importance of personalized, evidence-based approaches to optimize treatment selection and enhance patient care..